Implementation of Kegel Exercises for Pregnant Women with Urinary Incontinence in the Third Trimester at Kahuripan Public Health Center, Tasikmalaya - Sambas, Etty Komariah; Nurliawati, Enok; Salsabilla, Talitha Agripina; Yuningsih, Aneng (KIAN JOURNAL, 2025)
Introduction: Third trimester pregnancy is often accompanied by physical discomfort such as urinary incontinence, which affects the quality of life of pregnant women. Kegel exercises are one of the exercises that can help overcome this problem by strengthening the pelvic floor muscles and bladder sphincter. This study aims to determine the effect of Kegel exercises on urinary incontinence in third trimester pregnant women in the working area of Kahuripan Community Health Center, Tasikmalaya City. Objective: This study aimed to determine the response of changes in third trimester pregnant women who experience urinary incontinence after implementing Kegel exercises for three consecutive days. Methods: This study used a case study design with two pregnant women in their third trimester experiencing urinary incontinence. Data were collected through interviews, physical examinations, and observations before and after the Kegel exercise intervention. Kegel exercises were performed three times a day for three consecutive days. Data were analyzed descriptively by measuring changes in urinary frequency, nocturia, enuresis, and bladder distension. Results: Before the intervention, both subjects experienced an increase in urinary frequency, nocturia, enuresis, and bladder distension. After three days of Kegel exercises, there was a significant decrease in all these parameters, with increased control of the pelvic floor muscles and bladder sphincter. Conclusion: Regular Kegel exercises can effectively reduce urinary incontinence in pregnant women in the third trimester. This intervention can improve the quality of life of pregnant women by improving urinary frequency, nocturia, enuresis, and bladder distension. It is recommended that pregnant women independently perform Kegel exercises as a preventative and treatment measure for urinary incontinence during pregnancy.